The dearth of feminist empirical research on women’s active participation in the ICT sector - Naledi Sekeleni; Carol Lesame (Communicare)
This paper seeks to create awareness of the need for research academics and practitioners involved in the ICT field collaborate in co-producing feminist empirical research studies that integrate theory and practice (evidence-based) when doing research on the circumstance related to women’s entrepreneurship and intrapreneurship in the context of the Eastern Cape Province in South Africa, which is under scrutiny. The notion of cross-professional collaboration is triggered by recommendations extrapolated from a qualitative case study conducted on the ICT sector in the Eastern Cape, wherein the findings allude to a gap in empirical research studies employing feminist epistemological and methodological norms of inquiry in examining women’s entrepreneurial and intrapreneurial activities. This paper advances the view that initiating a trend within the researcher community, where follow-up studies are conducted from research recommendations, will stimulate reflection and debate around empirically grounded feminist scholarship in an emerging and unexplored field of research, namely women’s entrepreneurship and intrapreneurship, in both urban and rural settings of the ICT sector.